Violence in the City : Understanding and Supporting Community Responses to Urban Violence - World Bank (Washington, DC, 2017)
This study aims to understand how urban residents cope with violence, or the threat of it, in their everyday lives, to inform the design of policies and programs for violence prevention. The study is the first global study on urban violence undertaken by the World Bank and covers three regions. It emerged from the growing demand within the Bank and client governments for a more comprehensive understanding of the social dimensions of urban violence. The study is not an exhaustive review of the topic, but rather is an exploration of the social drivers of violence, and its impact on social relations. The report consists of six chapters. In chapter one, the topic of urban violence is introduced as a pressing development issue. Chapter two discusses the complex relationship between cities and violence. In chapter three, the report reviews the literature to develop an analytical framework for understanding community capacities for violence prevention. Chapter four reviews interventions to prevent violence in terms of their impact on these key community capacities. The empirical findings from the five case studies are presented in chapter five, followed by strategic policy orientations in chapter six.